Increasing profitability in a South African mining supply company by applying the theory of constraints - Macauley, Denzyl James (My University, 2018)
This project was identified as the applied research project to fulfil my qualification for the Master of Business Administration. The focus is grounded on the Theory of Constraints as depicted in the book entitled “The Goal” by Eliyahu M. Goldratt and Jeff Cox. The aim of this work was to establish ways to grow the injection moulding screen panel manufacturing business post the next 3 years by evaluating opportunities to increase throughput. Data was collected to determine lost time in production processes and the impact it has on throughput. Time lost contributing to production downtime was found to be as a result of machine tool changes, meetings and machine breakdowns. After establishing the throughput which could be realised by addressing these areas of consideration, recommendations were made to improve follow up activities to cope with additional throughput. When inventory was evaluated, it was found that a substantial amount of money is tied up due to a raw material overstock situation existing. Discussions will be held with suppliers to take ownership of management of raw materials and this can have a positive effect on the cash flow of the business as a whole. The Theory of Constraints is grounded on the fact that any changes made to a bottleneck in a process must have a meaningful financial contribution towards the operation of a production facility and all other prior and follow up activities. Even though most individuals within the organisation including myself feels that a reduction in downtime to increase throughput in this particular scenario can have a meaningful contribution to grow the business, it was found to not be true due to the effect on operating profit. If Multotec want to grow their business by 10% year on year for the next 3 years, it is recommended to invest in machines to generate throughput in order to have a meaningful profit contribution. In addition to this, a continuous 24 hour shift cycle inclusive of weekends & holidays will have a similar effect on profit without requiring investment in immediate terms. 2 Post the 3 year term, Multotec will have to penetrate global markets aggressively as a growth strategy to further exploit financial benefit in the screening mining markets, and the best way to do this is to partner with sister companies having existing footprint.
MBA
Keywords: Gold mines and mining -- South Africa. Labor supply -- South Africa. Mineral industries.